Effect of Sapium indicum, Thevetia neriifolia and Jatropha gossypifolia Seed Extract on the Fecundity and Fertility of Tribolium castaneum and Tribolium confusum - Khanam, LA Muslima; Khan, AR; Khalequzzaman, M; Rahman, SM (Bangladesh Journal of Scientific and Industrial Research, 2008)
An experiment has been conducted to find out the toxic effect of acetone extract of Sapium indicum seed, petroleum ether extract of Thevetia neriifolia seed kernel and Jatropha gossypifolia seed on the fecundity and fertility of Tribolium castaneum and Tribolium confusum. The results indicated that all the treatments significantly (P < 0.001) reduced the fecundity and fertility of both the insect species. However Jatropha gossypifolia seed extract did not reduce significantly the fertility of Tribolium castaneum in comparison with the control but a decline of fertility was observed with the increase of dose of treatment. Key word: Seed extracts, T. castaneum, T. confusum, Fecundity and Fertility. DOI: 10.3329.bjsir.v43i1.857 Bangladesh J. Sci. Ind. Res. 43(1), 55-66, 2008